THE USE OF MULTIMEDIA TECHNOLOGIES IN ENGLISH LESSONS (American Journal of Pedagogical and Educational Research, 2026)
In recent years, the question of the use of new multimedia technologies in education has been increasingly raised. These are not only new technical means, but also new forms and methods of teaching, a new approach to the learning process. The main goal of teaching foreign languages is the formation and development of a communicative culture of students, teaching practical mastery of a foreign language.